1985
DOI: 10.1210/endo-117-4-1456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aluminum on Bovine Parathyroid Adenylate Cyclase*

Abstract: It is known that the secretion of PTH is often impaired in association with aluminum (Al3+) accumulation in patients with renal failure. The mechanisms involved remain ill defined. Since adenylate cyclase plays a role in the regulation of PTH secretion, these studies examine the effects of Al3+ on parathyroid adenylate cyclase. In membranes from normal bovine parathyroid glands, basal adenylate cyclase activity, in the presence of 0.2 mM ATP and 20 mM Mg2+, increased by 22% as Al3+ was raised from 0-10 microM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

1988
1988
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…First, it has been recently shown using in vitro techniques that the secretion of PTH by collagenase-dispersed bovine parathyroid cells or by tissue slices of porcine parathyroid glands is inhibited when these pre parations are incubated in media containing aluminum in concentrations comparable to those seen in patients on hemodialysis [22][23][24]. Furthermore, a decreased respon siveness of the parathyroid glands to hypocalcemia has been observed in patients with osteomalacia and evi dence of bone aluminum deposition [38].…”
Section: Effects On Plasma Calcium and Aluminum Levels And On Parathmentioning
confidence: 99%
See 2 more Smart Citations
“…First, it has been recently shown using in vitro techniques that the secretion of PTH by collagenase-dispersed bovine parathyroid cells or by tissue slices of porcine parathyroid glands is inhibited when these pre parations are incubated in media containing aluminum in concentrations comparable to those seen in patients on hemodialysis [22][23][24]. Furthermore, a decreased respon siveness of the parathyroid glands to hypocalcemia has been observed in patients with osteomalacia and evi dence of bone aluminum deposition [38].…”
Section: Effects On Plasma Calcium and Aluminum Levels And On Parathmentioning
confidence: 99%
“…We recognize that in our patients the simple discontinuation of aluminum intake for a period of 3 weeks is not likely to have caused a substantial decrement in total body aluminum content. However, the decrease in plasma aluminum levels may have been correlated with a decrease in the amount of readily ex changeable aluminum strategically located in the parath yroid glands where it exerts its suppressive action upon the activity of adenylate cyclase [23,39], This would then result in an increased secretion of PTH despite the con current increase in serum calcium concentration.…”
Section: Effects On Plasma Calcium and Aluminum Levels And On Parathmentioning
confidence: 99%
See 1 more Smart Citation
“…Such ef fects may inhibit molecular interactions on the sur face of lymphocytes, decrease the mobility of phago cytic cells and halt metabolic processes by making ATP unavailable for use, thereby increasing suscep tibility to bacterial challenge. However, Al may also decrease cAMP synthesis, increase cGMP produc tion, cause the release of intracellular calcium stores, stimulate the metabolism of phosphotidylinositols and initiate the phosphorylation of T cell receptors [5,7], These latter studies provide the basis for an understanding of how Al may increase immune re sponsiveness, including the means by which Al may act as an immunological adjuvant. In fact, Al has been shown to enhance antigen-presenting activ ity [27], suggesting that one effect of Al adjuvants in vaccines is to alter cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…These clinical and environmental obser vations, combined with the knowledge that this metal is used as a component in many consumer products, motivated the initiation of studies on the biological consequences of excess Al exposure [1][2][3]. For exam ple, among 29 metals examined in vitro, only beryl lium and Al (1-5 pAf), complexed with fluoride ion, were able to activate G proteins and thereby regulate adenylate cyclase activity [4], At higher concentra tions (> 10 pi A/), Al was also shown to inactivate ad enylate cyclase [5]. Other work has pointed to the pos sible involvement of Al in the production of cyclic GMP [6] as well as the phosphatidylinositol secondmessenger pathway [7], Al hydroxide is well known as an immunological adjuvant and Al has been shown to activate lymphoid cell functions [7,8], Animal exposure studies have also shown that Al can modify mast cell function [9], induce splenic suppressor macrophages [10] and acti vate complement [11], We report herein that Al can af fect susceptibility of mice to infection by Listeria monocytogenes.…”
Section: Introductionmentioning
confidence: 99%